Accounting for Coastal Sustainability: A Political Economy Analysis of Environmental Cost Distribution and Local Governance - Ulfi Hanifah, Risti; Safitri, Candra; Sahri Romadon, Ahmad; Akriana Nila Relita, Fajar (Inovasi Analisis Data, 2025)
Purpose - This study examines the integration of green accounting practices and participatory governance mechanisms in advancing sustainable village development in Indonesia.Design/methodology/approach - A mixed-methods approach combining quantitative surveys and qualitative case studies was employed across 15 villages in Central Java to analyze the interconnected roles of environmental accounting systems and community participation.Findings - The results indicate that villages implementing comprehensive green accounting frameworks demonstrate 35% better environmental outcomes and 28% higher community satisfaction. Participatory governance structures significantly enhance transparency and resource allocation efficiency.Originality/value - This research contributes to sustainable development literature by providing empirical evidence of accounting-governance synergies at the local level and offers a unified framework for integrating environmental and social dimensions.Research implications - The findings offer theoretical insights for advancing research on sustainable rural development and provide practical guidance for policymakers seeking to implement integrated environmental accounting systems.